2017
DOI: 10.1144/sp463.6
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of modal metasomatism in the post-Deccan subcontinental lithospheric mantle: petrological evidence from an ultramafic xenolith in an Eocene lamprophyre, NW India

Abstract: We report here on the occurrence of an interesting mantle-derived ultramafic xenolith entrained in an Eocene (c. 55 Ma) lamprophyre dyke from the Dongargaon area of the Chhotaudepur alkaline subprovince located within the Narmada Rift Zone, NW India. The mineralogy of the xenolith comprises olivine, clinopyroxene and mica (phlogopite), with the latter occurring essentially as rims around the clinopyroxene. Inclusions of apatite, interstitial sulphide (pyrite) and micron-scale exsolved spinel are widespread. Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The compositional variations of the major minerals such as plagioclase, hornblende, and biotite amongst the host granite, hybrid rock (mixed After repeated analyses, it was found that the error on major element concentrations is <1%, whereas the error on trace elements varied between 3% and 5% (Pandey, Rao, Pandit, Sahoo, & Dhote, 2018).…”
Section: Mineral Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The compositional variations of the major minerals such as plagioclase, hornblende, and biotite amongst the host granite, hybrid rock (mixed After repeated analyses, it was found that the error on major element concentrations is <1%, whereas the error on trace elements varied between 3% and 5% (Pandey, Rao, Pandit, Sahoo, & Dhote, 2018).…”
Section: Mineral Chemistrymentioning
confidence: 99%
“…A number of natural and synthetic standards were used for calibration. After repeated analyses, it was found that the error on major element concentrations is <1%, whereas the error on trace elements varied between 3% and 5% (Pandey, Rao, Pandit, Sahoo, & Dhote, ). Line scans across the minerals were also conducted to infer the elemental distribution and compositional variation, respectively.…”
Section: Mineral Chemistrymentioning
confidence: 99%
“…A restricted range in the major oxide composition variation for these lamprophyres suggests they are likely to be a part of a single magmatic episode. Subba Rao et al (1989) have reported Rb-Sr isochron age of the (Madhavan et al, 1998;Madhavan et al, 1992;Upadhyay et al, 2006;Vijaya Kumar and Rathna, 2008); Deccan LIP (Hari et al, 1998;Melluso et al, 2012;Dessai and Vegas, 2010;Pandey et al, 2017c); Mahakoshal (Srivastava and Chalapathi Rao, 2007;Srivastava, 2013) Gondwana Coalfield (Srivastava et al, 2009Chalapathi Rao et al, 2014); Eastern Dharwar Craton (Meshram et al, 2015, Pandey et al, 2018b, Pandey et al, 2017aLanjewar and Randive, 2017). Fig.…”
Section: Eastern Dharwar Craton Lamprophyresmentioning
confidence: 99%
“…7, 8). Pandey et al (2017aPandey et al ( , 2018b have suggested the presence of a subduction modified mantle wedge in the SCLM beneath EDC, probably, as a result of Neoarchean accretion related Subrahmanyam et al, 1987;Madhavan et al, 1992Madhavan et al, , 1998Ratnakar et al, 1996;Vijaya Kumar and Rathna, 2008), Mahakoshal (Srivastava and Chalapathi Rao, 2007;Srivastava, 2013), Eastern Dharwar Craton (Meshram et al, 2015;Lanjewar and Randive, 2017;Pandey et al, 2017aPandey et al, , b, 2018b, Deccan LIP (Dessai and Vegas, 2010;Pandey et al, 2017c), and Gondwana coalfield (Srivastava et al, 2009;Chalapathi Rao et al, 2014). growth of the Dharwar Craton (Jayananda et al, 2018 and references therein).…”
Section: Figure 5 Tio 2 (Wt %) Vs Sio 2 (Wt %) Plot Comparing Amphibmentioning
confidence: 99%
“…The CAMECA SXFive instrument was operated by SXFive Software at a voltage of 25‐kV current 10 nA for major elements and 40 nA for rare earth elements (REEs) with a LaB 6 filament in the electron gun for generation of electron beam and beam diameter of 1 μm. The natural and synthetic standards used for calibration are same as given in the study of R. Pandey et al (). Counting time for major and minor elements were 10 and 60 s for the REEs.…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 99%